2019
DOI: 10.1038/s41467-019-13017-4
|View full text |Cite
|
Sign up to set email alerts
|

IL-27 receptor-regulated stress myelopoiesis drives abdominal aortic aneurysm development

Abstract: Abdominal aortic aneurysm (AAA) is a prevalent life-threatening disease, where aortic wall degradation is mediated by accumulated immune cells. Although cytokines regulate inflammation within the aorta, their contribution to AAA via distant alterations, particularly in the control of hematopoietic stem cell (HSC) differentiation, remains poorly defined. Here we report a pathogenic role for the interleukin-27 receptor (IL-27R) in AAA, as genetic ablation of IL-27R protects mice from the disease development. Mit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 71 publications
1
32
0
1
Order By: Relevance
“…Only one recent animal study reported that deletion of IL-27R reduced the formation of abdominal aortic aneurysm in ApoE deficiency mice, the mechanisms may be associated with a blunted accumulation of myeloid cells in the aorta (Peshkova et al, 2019).…”
Section: Interleukin-12 Family Members and Aortic Aneurysms And Aortimentioning
confidence: 99%
“…Only one recent animal study reported that deletion of IL-27R reduced the formation of abdominal aortic aneurysm in ApoE deficiency mice, the mechanisms may be associated with a blunted accumulation of myeloid cells in the aorta (Peshkova et al, 2019).…”
Section: Interleukin-12 Family Members and Aortic Aneurysms And Aortimentioning
confidence: 99%
“…In sepsis patients, IL-27 promoted the inflammatory response and aggravated liver damage [38]. IL-27Rα deficiency could protect abdominal aortic aneurysm development through limiting accumulation of myeloid cells and Ang II-induced hematopoietic stem cell expedition [39]. These studies indicated that the IL-27Rα signal plays a pro-inflammation role.…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown that the level of IL27 in blood is possibly an important marker for assessing the rate of HSC aging [ 232 ]. An increase in the IL27 concentration also leads to stress myelopoiesis resulting in the development of abdominal aortic lesions [ 233 ]. IL27 levels have been shown to be minimal in early childhood, but the peak of cytokine production by dendritic cells occurs during adulthood and possibly at old age [ 234 ].…”
Section: Age-associated Inflammatory Factorsmentioning
confidence: 99%